Dinâmica de moléculas pesticidas em lisímetro cultivado com milho (Zea mays L.) em sistema de sucessão de culturas - Conradi Junior, Elio (2023)
After their insertion into the environment, pesticide molecules are subject to different processes that can influence the fate of these substances in different environmental compartments. In this context, studies on the molecular interactions of pesticides used in agriculture in different crops under different edaphoclimatic conditions are important for assessing possible environmental problems arising from the use and application of these substances. Thus, the objective of this study was to evaluate the transport of pesticides and their environmental distribution in the edaphoclimatic conditions of Marechal Cândido Rondon, state of Paraná, by determining the surface runoff and percolation of the herbicide atrazine and the insecticide thiamethoxam in the corn crop , in Red Latosol. As this is an environmental study, the field work was carried out during an agricultural year (2020/2021), with the cultivation of a corn crop, inserted in the crop succession system (soybean/corn), and the concentration of molecules in different matrices (soil, plant and water) and the possibility of contamination of surface and groundwater. For this, a percolation lysimeter was used with an undisturbed soil sample (1 m³). The transport of atrazine and thiamethoxam was evaluated under the influence of simulated precipitation (150 mm h-¹), 24 and 48 h after pesticide spraying, carried out 17 days after corn emergence, adopting dose and number of applications according to with the technical recommendations of the respective commercial products. In the laboratory, granulometric and chemical characterization of the soil was carried out, as well as studies of sorption and dissipation of the insecticide and evaluation of physical and chemical attributes in the volumes of surface runoff and percolated water. Pesticide determinations were performed by ultra performance liquid chromatography with diode array detector (UPLC-DAD). Nonlinear Freundlich isotherms showed an excellent fit in the description of atrazine sorption in an Oxisol. The organic matter content in the soil influences the sorption process, however the temperature has little importance in the retention of the herbicide. The half-life (T1/2) of atrazine in soil under controlled conditions indicates a non-persistent pesticide, with 8.82 days. However, the herbicide can persist in deep soil layers for more than 76 days after spraying. When heavy rainfall occurs 24 hours after application, large proportions of atrazine are lost to runoff within the first 20 minutes of rainfall. At the same time, significantly lower losses are observed when precipitation occurs 48 h after spraying. Rain events 24 h after atrazine application can cause losses of up to 84% in maize leaves and 94% in soil. In the sorption study involving the insecticide thiamethoxam in an Oxisol, a good fit was obtained for non-linear Freundlich isotherms. Thiamethoxam has low sorting capacity with Kf values ranging from 0.587 to 1.385. Furthermore, values of 1/n close to 1 are observed, which suggests that the pesticide is irreversibly adsorbed to soil colloids in calcined and non-calcined soil samples. The oxides and hydroxides of iron and aluminum present in the Red Latosol are of great importance in the retention of the pesticide, followed by the content of organic matter in the soil. Despite variations in the average sorbed and Kf values, increasing the system temperature has little effect on the sorption process in soil samples with or without organic matter. The study shows that due to the sorption of thiamethoxam to the surface layer of the soil, and the short half-life of the molecule in soil and plants (non-persistent), there may be a reduction in the risk of environmental contamination. The results indicate a low possibility of contamination of surface or groundwater under the conditions studied (spraying according to agronomic recommendations), even in conditions of intense precipitation 24 and 48 h after spraying the insecticide on the corn crop. Conservationist agronomic practices that protect the soil, especially in the early stages of maize cultivation, are essential to reduce the erosion process, aiming to mitigate soil loss and the possibility of contamination of water resources by atrazine and thiamethoxam via surface runoff.